Analysis of Students' Reasoning Ability, Mathematical Connections, Self-Efficacy, and Difficulties in Solving Probability Story Problems - Puspitasari, Ratna; Hidayati, Kana (FONDATIA, 2024)
This research aims to describe reasoning abilities, mathematical connections and self-efficacy as well as the difficulties faced in solving opportunity material story problems in each category of reasoning ability, mathematical connections and self-efficacy. The type of research used is survey research with a quantitative and qualitative approach. The population of this study were all public junior high school students in Sleman Regency, Yogyakarta. The research sample was taken using a proportional stratified random sampling technique with a sample size of 384 students. The results showed that students' mathematical reasoning abilities were included in the medium category with an average value of 57.92 to 60.52, students' mathematical connection abilities were included in the medium category with an average value of 59.64 to 62.98, students' self-efficacy included in the medium category with an average value of 68.35 to 70.41.